Stages of Self-Help Organization Development: Women Farmers Group D’Shafa in Malakasari Urban Village, Duren Sawit District, East Jakarta - Shakilla Dyah Ayu Nadira; Binahayati Rusyidi; Eva Nuriyah Hidayat (Edumaspul: Jurnal Pendidikan, 2025)
The D’Shafa Women Farmers Group (Kelompok Wanita Tani/KWT D’Shafa) is a community-based self-help organization that has developed since its establishment in 2018 in RW 05, Malakasari Urban Village, Duren Sawit District, East Jakarta. Through various urban farming activities, the group focuses on food security and women’s empowerment within the local community. This study aims to describe the developmental stages of KWT D’Shafa using Katz’s organizational development theory (as cited in Adams, 2003), as well as to identify the internal and external factors that support its sustainability. This research employs a descriptive qualitative approach, with data collected through in-depth interviews, participatory observation, and document analysis involving the group’s leaders, administrators, members, and external partners. The findings show that KWT D’Shafa has gone through five developmental stages according to Katz, including origins, informal organization, emergence of leadership, beginning of formal organization, and progressing toward the stage of appointing paid staff and professional workers. However, the group has not fully reached the final stage, as it does not yet employ paid staff, and professionalization efforts still rely on voluntary collaboration with external experts. These findings indicate that the sustainability of KWT D’Shafa is supported by internal factors such as social interaction, participatory leadership, and member commitment, as well as external factors including government assistance and private-sector partnerships, which together enable the group to continue growing as a self-help organization in an urban environment.